The role of cGAS-STING signaling in pulmonary fibrosis and its therapeutic potential - Zhang, Jing; Zhang, Lanlan; Chen, Yutian; Fang, Xiaobin; Li, Bo; Mo, Chunheng (Frontiers in Immunology, 2023)
Pulmonary fibrosis is a progressive and ultimately fatal lung disease, exhibiting the excessive production of extracellular matrix and aberrant activation of fibroblast. While Pirfenidone and Nintedanib are FDA-approved drugs that can slow down the progression of pulmonary fibrosis, they are unable to reverse the disease. Therefore, there is an urgent demand to develop more efficient therapeutic approaches for pulmonary fibrosis. The intracellular DNA sensor called cyclic guanosine monophosphate-adenosine monophosphate (cGAMP) synthase (cGAS) plays a crucial role in detecting DNA and generating cGAMP, a second messenger. Subsequently, cGAMP triggers the activation of stimulator of interferon genes (STING), initiating a signaling cascade that leads to the stimulation of type I interferons and other signaling molecules involved in immune responses. Recent studies have highlighted the involvement of aberrant activation of cGAS-STING contributes to fibrotic lung diseases. This review aims to provide a comprehensive summary of the current knowledge regarding the role of cGAS-STING pathway in pulmonary fibrosis. Moreover, we discuss the potential therapeutic implications of targeting the cGAS-STING pathway, including the utilization of inhibitors of cGAS and STING.